The communicative language teaching activities to develop english language speaking skills among students of ninth –year "b" afternoon session at Miguel Riofrío basic education school in the city of loja during the 2018−2019 academic year - Jimenez Navarro, Yaritza del Cisne (2019)
The main objective of the research was to develop the English Language speaking skills using the communicative language teaching activities. To develop this research, it used the scientific, descriptive, statistical, and analytical / synthetic method to collect theoretical references, explain speech skills, tabulate information and analyze and interpret the results obtained. The instruments used were: tests, questionnaires that were applied to twenty-seven students to diagnose the level of knowledge, field notes and observation sheets were also used to see the progress of the students. The results showed that the students developed their speaking skills significantly in the following aspects: vocabulary, grammar, pronunciation, fluency and comprehension. As a main conclusion, the application of the teaching activities of the communicative language had a positive development in the students, since they overcame their fear to speak in English and were able to participate and interact frequently